Lewis. Bob. Interview about the early days of radio in Newfoundland and Labrador. - Swain, Hector K. (1990)
Bob Lewis talks about working with CJON and the early days of radio broadcasting in Newfoundland. 00:00 - Talks about meeting Bill Goudie in 1929 at Ayres and Sons. Goudie had studied as a Christian Brother but did not continue at Mount Cashel. 02:30 - Talks about a radio station on Bell Island around 1930; 4:10 - Talks about a Sanitorium radio that patients would use to send messages home. The speaker would take a microphone and go to the different departments and talks to people; 5:30 - Broadcasting the Salvation Army Band; 07:33 - Talks about Aubrey “Mac” Macdonald; 9:24 - [Tape cuts out and starts again, may be another interviewee. The following section is an interview with Bob Lewis];10:00 - Talk about the early days of radio; CJON started in 1951 but Lewis came the year after; Programming; 18:27 - Talks about Christmas; Religious programming; 22:38 - The Fort Pepperrell radio station; 26:30 - Talks about giving out personal messages from people sending messages back home; 28:33 - Talks about messages being news, weddings, births, deaths, etc; Talks about a message that stands out in his memory; 31:30 - Talk about the radiotelephone network; 32:25 - Talks about Rev. Lester Burry and amature radio; 35:18 - The Lidstone Sisters; 36:26 - Talks about the equipment they used and Rollie Peddle; 37:15 - VOWR and VOAR, talks about licensing changes with confederation; 39:10 - Talk about radio stations owned by Geoff Stirling; 42:00 - Newfoundland as a birthplace of modern day communications;